Status of raptors in turahalli minor forest, Bangalore, Karnataka, India - Ashwini, R; Kumara, Vijaya (Indian Forester, 2022)
Present study was conducted at Turahalli minor forest, Bangalore to understand the status of raptors in forest habitats. Observational investigations of avian studies were carried out using field binoculars and DSLR camera and line transect method was adopted for bird counting. Total fifteen species of raptors belonging to Falconidae, Accipitridae and Strigidae families were recorded during study period i.e. ’March 2019 to Dec 2021’. Black kite and Brahminy kite have highest population and most dominant species in the study site, whereas common kestrel, Besra, Changeable hawk eagle was rarely observed. Field study was conducted in three different seasons summer, winter and rainy. Maximum number of individuals were recorded during summer (171) followed by winter (141) and rainy (50) season respectively. Data were analyzed using Shannon-wiener diversity Index, species diversity (H=1.875), species richness (SR=2.376) and evenness (E=0.4336). In winter species diversity was more (1.976) followed by summer (1.741) and rainy (1.523) season. In terms of distribution status of raptors 79% were resident, 14% winter visitor, 7% partial visitors.